Maternal and perinatal outcomes, and associated factors in isolated borderline oligohydramnios: a cross-sectional analytical study - S., Roshini; Gayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Borderline oligohydramnios is associated with adverse perinatal outcomes. This study aimed to assess the impact of borderline oligohydramnios on maternal and perinatal outcomes, focusing on mode of delivery, fetal distress, neonatal morbidity, and NICU admissions. Methods: A cross sectional analytical study comprising 80 antenatal mothers (≥34 weeks) with borderline oligohydramnios was conducted at an Indian hospital. Data were collected through a semi-structured questionnaire and case record reviews. Maternal and perinatal outcomes were analyzed, including mode of onset and delivery, Apgar scores, NICU admissions, and neonatal morbidity. Results: The mean (SD) age of the participants was 24.5 (2.1) years. Induced labor was prevalent (41%), with 7% of infants experiencing neonatal morbidity, mainly meconium aspiration and neonatal sepsis. About 60% (n=40) delivered a baby between a weight 2.5 to 3 kg, 63% (n=50) had APGAR score more than 7, 34% (n=27) admitted to neonatal intensive care units, and the main reason for NICU admission was fetal distress (n=44.4%). The reason for neonatal morbidity was meconium aspiration (5%) followed by neonatal sepsis (2.5%). Non-reassuring NST and amniotic fluid nature significantly correlated with NICU admissions, while age and AFI influenced delivery mode. Conclusions: Borderline oligohydramnios led to a high rate of induced labor, yet neonatal morbidity was relatively low. Non-reassuring NST and amniotic fluid nature significantly impacted NICU admissions. Further research on a larger scale is warranted to validate these findings for widespread implementation.